APLIKASI KURVA BEZIER PADA DESAIN BOTOL MINUMAN - Triadi, Muhammad Bagus Firman; Juliyanto, Bagus; Ubaidillah, Firdaus (Jurusan Matematika FMIPA Universitas Jember, 2020)
The beverage bottle consists of several parts. There are mouth, neck, shoulders and body of the beverage bottle. This study aims to modeled the shape of the beverage bottles use Bezier curves with degrees less than or equal to six (n ≤ 6), for obtain a varied and symmetrical shape of the beverage bottles. This research method are divided into several stages. First, modeled the mouth of the beverage bottle. Second, modeled the neck of the beverage bottle. Third, modeled the body of the beverage bottle. Fifth, combined the parts of the beverage bottle. The results of this study was obtained a procedure for modeled varied and symmetrical beverage bottles using Bezier curves with degrees less than or equal to six (n ≤ 6). Keywords: Beverage Bottle, Bezier Curve, Computer Aided Geometric Design